Analisis pendapatan kelompok nelayan melalui program bantuan kapal penangkapan ikan di Desa Toolawawo Kecamatan Lalonggasumeeto Kabupaten Konawe - Destriani, Restu; Yusuf, Sarini; Riani, Irdam (Universitas Halu Oleo, 2021)
This research aims to determine the impact of the fishing vessel assistance program on the income of fishermen in Toolawawo Village, Lalonggasumeeto District, Konawe Regency. One of the fishing facilities assistance programs is the 3 GT vessel, uses for collecting data from January-May 2020, the vessel was given to 4 fisherman asrespondents. The sampling technique in this study was total sampling. Data obtained through interviews using a questionnaire and analyzed by quantitative methods using the income formula. The results showed that the income of fisherman before receiving boat assistance was IDR 1,067,750/trip or IDR 3,203,250/month and after receiving assistance their income increased IDR 2,611,550/trip or IDR 7,834,650/month. This means that the 3 GT boat assistance program was able to increase fisherman's income by 40.9%.